Níveis de lactato sanguíneo, em futebolistas profissionais, verificados após o primeiro e o segundo tempos em partidas de futebol - Silva, Paulo Roberto Santos; Inarra, Luís Antonio; Vidal, José Roberto Rivelino; Oberg, Alexandre Augusto Ribeiro Barros; Fonseca Junior, Alcides; Roxo, Carla Dal Maso Nunes; Machado, Gilberto Silva; Teixeira, Alberto Azevedo Alves (Acta Fisiátrica, 2000)
Lactate blood levels in professional socer players after end of the first and second half in soccer matches The main purpose of this study was to assess the participation of the anaerobic lactic metabolism by measuring the lactate blood level in professional soccer players shortly after the end of the first and second half in soccer matches. The assessment was carried out in 26 male soccer players belonging to the Department of Professional Soccer at Associação Portuguesa de Desportos in São Paulo – Brazil. The group was composed of 4 full-backs, 13 midfielders and 9 forwards. Whose age, weight and stature ranged, respectively, from 18 to 33, from 56.5 kg to 78.5 kg and from 164 cm to 185 cm. The soccer players were piecked at random during the procedure. The lactate analyser used to this end was a portable (Accusport model, Boehringer Mannheim, Germany). These were the results: the average lactate level in all soccer players examined after the end of the first half and the second half of the matches analyzed was 7.1 mM ± 0.6 mM and 5.7 mM ± 1.3 mM (p < 0.05). When divided according to their position, the full-backs showed, respectively, 6.9 mM ± 2.9 mM and 4.7 mM ± 3.0 mM; the midfielders 6.4 mM ± 1.8 mM and 5.6 mM ± 1.2 mM and the forwards 7.7 mM ± 1.8 and 7.2 ± 2.1 mM. When we compared the lactate production according to the position, there was only significant statistic (p < 0.05) in the second half between the forwards 7.2 mM ± 2.1 mM and the midfielders 5.6 mM ± 1.2 mM, respectively. Conclusion: Subjective factors, such as movement rate, quick recovery and constant disposition during the match related to primary factors, such as reduced glycolitic activity and diminished muscular glycogen concentration caused by little specific lactic anaerobic training and/or poor diet, are evidences that can partly explain why the lactate blood level in the second half has often been lower when compared with the end of the first half of a soccer match.